Closed Reduction in Developmental Dysplasia of the Hip in Patients Older than One Year - Bozinovski, Zoran; Bogojevska Doksevska, Milena; Tokmakova, Keti P (Pensoft Publishers, 2020)
Besides an effective screening method for developmental dysplasia of the hip, there is certain number of children in whom the condition has been overseen or they have never been screened and the parents have noticed the odd walking pattern in their toddler. Treatment of such patients is controversial. One of the recommended treatment methods because of the short-term hospitalization, but often considered unsuccessful is closed reduction of the hip followed by cast immobilization.